Analysis of the Modified Rankin Scale in Randomised Controlled Trials of Acute Ischaemic Stroke: A Systematic Review. (20th March 2016) - Nunn, Aimie; Bath, Philip M.; Gray, Laura J.
Abstract : Background . Historically, most acute stroke clinical trials were neutral statistically, with trials typically dichotomising ordinal scales, such as the modified Rankin Scale. Studies published before 2007 have shown that preserving the ordinal nature of these scales increased statistical power. A systematic review of trials published since 2007 was conducted to reevaluate statistical methods used and to assess whether practice has changed. Methods . A search of electronic databases identified RCTs published between January 2007 and July 2014 in acute ischaemic stroke using an ordinal dependency scale as the primary outcome. Findings . Forty-two RCTs were identified. The majority used a dichotomous analysis (25, 59.5%), eight (21.4%) retained the ordinal scale, and nine (19.0%) used another type of analysis. Conclusions . Trials published since 2007 still favoured dichotomous analyses over ordinal. Stroke trials, where appropriate, should consider retaining the ordinal nature of dependency scales.